Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/dth.12437
|View full text |Cite
|
Sign up to set email alerts
|

Platelets rich plasma versus minoxidil 5% in treatment of alopecia areata: A trichoscopic evaluation

Abstract: Alopecia areata is a common cause of nonscarring alopecia that occurs in a patchy, confluent, or diffuse pattern. Dermoscopy is a noninvasive technique for the clinical diagnosis of many skin diseases. Topical minoxidil solution 5% and platelet rich plasma are important modalities used in treatment of alopecia areata. We aimed to evaluate the efficacy of PRP versus topical minoxidil 5% in the treatment of AA by clinical evaluation and trichoscopic examination. Ninety patients were allocated into three groups; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 34 publications
(44 reference statements)
9
82
1
3
Order By: Relevance
“…The role of trichoscopy in the therapeutic monitoring of alopecia areata was also emphasized . Hegde et al .…”
Section: Trichoscopy In Monitoring Treatment Efficacy Of Alopecia Areatamentioning
confidence: 99%
See 1 more Smart Citation
“…The role of trichoscopy in the therapeutic monitoring of alopecia areata was also emphasized . Hegde et al .…”
Section: Trichoscopy In Monitoring Treatment Efficacy Of Alopecia Areatamentioning
confidence: 99%
“…reported a reduction in exclamation mark hairs, black dots, yellow dots and broken hairs combined with an increased number of short vellus hairs and new vessels in patients with alopecia areata treated with diphenylcyclopropenone. According to El Taieb et al ., patients with alopecia areata treated with 5% minoxidil solution presented an increased number of short vellus hairs and decreased number of yellow dots. However, an increased number of fully pigmented hairs and the reduction in short vellus hairs and yellow dots were reported in patients treated with platelet‐rich plasma.…”
Section: Trichoscopy In Monitoring Treatment Efficacy Of Alopecia Areatamentioning
confidence: 99%
“…Contrasted with TrA and placebo, PRP showed more effective on the treatment of AA . Another study to evaluate the efficacy of PRP versus topical minoxidil 5% in the treatment of AA with 90 patients was carried out recently . While they both have significant improvements in hair growth, the PRP‐treated ones had earlier new hair regrowth and better new hair quality than the other two groups.…”
Section: Application Of Prpmentioning
confidence: 99%
“…For example, an intra‐control half head treatment study on AGA patients using PRP and placebo showed a statistically significant improvement in the number of anagen hairs in the target area and in total hair density post‐treatment . Pilot studies have also evaluated the efficacy of PRP for treating alopecia areata and were found to improve hair growth . Recent reviews of PRP for the treatment of hair loss conclude that, though clearly still in a nascent stage, the use of PRP for alopecia is promising and the side effects are relatively limited …”
Section: Introductionmentioning
confidence: 99%